Development Strategy Of Cv Zahra's Mononitrate Oil Umkm Through Digital Marketing In Sumbu Berastagi Village, Karo Regency - Widia Br Ginting; Dian Septiana Sari; Eadi Lubis (Journal of Management, Economic, and Accounting, 2026)
CV Zahra, a producer of traditional Karo herbal oil, has significant potential for growth and market expansion. The monitor lizard oil produced is of superior quality due to its natural ingredients, traditional processing, and legality from the Health Department. This factor is a key strength that differentiates CV Zahra from its competitors, especially amidst the growing trend of a healthy lifestyle returning to natural products. A SWOT analysis shows that CV Zahra is in Quadrant I (Aggressive Strategy), indicating that the business has sufficient internal strength to capitalize on available external opportunities. This demonstrates that CV Zahra is in a relatively advantageous position, where the most appropriate strategy is an aggressive strategy of market expansion, product innovation, and branding strengthening. However, internal weaknesses such as limited capital, production equipment, and digital marketing skills need to be addressed immediately, as do external threats such as competition from other popular herbal products and the rise of adulterated products that risk reducing consumer trust. By maximizing strengths and opportunities, while simultaneously improving weaknesses and anticipating threats, CV Zahra has the potential to not only maintain its presence in the local market, but also penetrate national and even international markets.